A multi-method approach to design urban logistics hubs for cooperative use. (June 2021) - Russo, Sonja M.; Voegl, Jana; Hirsch, Patrick
Highlights: Stakeholder groups pursue different goals for cooperative urban logistics hubs. Convergence among stakeholder groups is evident regarding environmental concerns. 45 attributes and indicator values describe three urban logistics hub user types. Empirical results serve as input to an optimisation model for hub space assignment. Hub space assignment depends on the political and civic vision of city development. Abstract: Limited availability of public space and high urban property prices make shared logistics solutions highly attractive. The objective of this paper is to offer guidance on the best way to design urban logistics hubs for cooperative use by different courier-, express and parcel service providers (CEPs). The present research used a set of different methods to collect a substantial amount of qualitative and quantitative data. The example of Vienna (Austria) offers real-world data. The research paper identifies suitable attributes for describing different CEP user types and uses a linear optimisation model to suggest an optimal allocation of the shared infrastructure capacity. The optimisation model aims to maximise the total utility of hub space utilisation throughout an average working day. It assumes that the utility increases with the hub's occupancy rate and the convergence of its CEP user types with the administration's and the citizens' vision of future city development. The results show that involved stakeholder groups – i.e. CEPs, citizens and city administrations – have both, conflicting and common goals.